Service life design and modelling of concrete structures – background, developments, and implementation - Alexander, Mark Gavin (Revista ALCONPAT, 2018)
The paper presents an international overview of current knowledge and progress in service life design and modelling of concrete structures. It explores why service life modelling is needed, and indicates that modern demands for longevity, durability, and sustainability of concrete structures cannot be fulfilled without service life modelling. It addresses the current approaches to durability design and specification and concludes that a move to performance-based approaches is imperative for progress to be made. Examples from international experience are cited to illustrate progress that has been made. Lastly, the paper discusses ways of moving forward, recognizing that the philosophical bases are already in place in the form of general code formulations, but which need to be converted into useful approaches.